Pediatric case of conidiobolomycosis: A rare entity. Issue 1 (21st December 2021) - Gupta, Parakriti; Pilania, Rakesh Kumar; Kaur, Harsimran; Rudramurthy, Shivaprakash Mandya; Soni, Ranu; Batra, Nitya; Verma, Roshan; Singh, Surjit; Chatterjee, Debajyoti
Abstract: Conidiobolomycosis caused by Conidiobolus species is an uncommon infection restricted to tropical and subtropical regions, usually affecting immunocompetent individuals. More than half of pediatric cases of conidiobolomycosis across the globe are from India. We report a case of subcutaneous conidiobolomycosis in an adolescent with development delay who responded to combined therapy with itraconazole and saturated solution of potassium iodide.